Superior 3DOM Y2Zr2O7 supports for Ni to fabricate highly active and selective catalysts for CO2 methanation. (1st June 2021) - Fang, Xiuzhong; Xia, Lianghui; Li, Shuobin; Hong, Zhou; Yang, Menghe; Xu, Xianglan; Xu, Junwei; Wang, Xiang
Graphical abstract: Highlights: 3DOM Y2 Zr2 O7 pyrochlore has been successfully fabricated for the first time. It possesses abundant hierarchically pores, big surface area and surface vacancy. NiO/Ni have a stronger interaction with it than with a regular Y2 Zr2 O7 -CP support. Ni/Y2 Zr2 O7 -3DOM owns both rich surface O2 − /basic sites and high active Ni surface. Thus it shows superior performance for CO2 methanation. Abstract: To fabricate CO2 methanation catalysts having application potentials, 3DOM structured Y2 Zr2 O7 pyrochlores with high surface area and hierarchically pores were prepared for the first time to support NiO/Ni. Compared with an Y2 Zr2 O7 -CP support synthesized by a co-precipitation method, NiO has a much stronger interaction with the Y2 Zr2 O7 -3DOM supports, thus achieving much higher active Ni surface after reducing. Furthermore, larger quantities of surface active O2 − /alkaline sites are also formed. The surface Ni sites can activate H2 molecules into adsorbed H atoms, and react with the CO2 molecules adsorbed on the surface O2 − /alkaline sites to form adsorbed CO, which will then be reduced by H atoms into CH4 . Therefore, the concerted interaction between surface active Ni and O2 − /alkaline sites determines the reaction performance. Ni/Y2 Zr2 O7 -3DOM700 owns abundant surface O2 − /alkaline sites and high active Ni surface, hence exhibiting superior reaction performance, which exceeds the literature reported catalysts up to date.